Diabetes mellitus and anxiety–Are they correlated? - MANJU ASWATH; RADHIKA MADHUSOODAN (International Journal of Pharma and Bio Sciences, 2018)
Diabetes is growing like epidemic and is associated with many psychiatric problems like depression and anxiety. The study was conducted to study the anxiety state in diabetics. Around 100 people (50- male: 25 diabetic and 25 Non diabetic as well as 50- female: 25 diabetic and 25 non diabetic) were enrolled in the study. Beck anxiety inventory was used to measure the anxiety level in the study population. The obtained data were analysed and interpreted using statistical tools such as mean, standard deviation, and t – test. On analysis, it was observed that there is statistically significant difference among diabetic and non-diabetic male group in relation to anxiety as compared to female participants with diabetic and non-diabetic but females were having slightly higher incidence and value on their anxiety scores. To conclude, the anxiety level was significantly higher in diabetic people both male as well as female.